2022
DOI: 10.3389/fcvm.2022.979982
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and atrial fibrillation risk: An updated dose-response meta-analysis of over 10 million participants

Abstract: BackgroundThe treatment of atrial fibrillation (AF) has made significant progress, but the prevention of AF has not received the attention it deserves. A few recent large-sized studies have conducted dose response analysis and reported different conclusions from previous studies on alcohol consumption and AF risk.ObjectivesThe aim of this study is to examine the potential non-linear association between alcohol consumption and risk of AF and explore the potential differences of gender.MethodsIn this updated dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…A relationship in the form of a "J" curve was found, as high alcohol consumption (>168 g/week) was significantly associated with an increased risk of AF, while moderate consumption (<168 g/week) was characterized by a protective effect [38]. However, the results of this meta-analysis were not confirmed in meta-analysis of 13 prospective studies, covering over 10 million subjects, conducted by Jiang et al [39]. This meta-analysis found that each increase in alcohol consumption by one drink/day is significantly associated with an increased risk of AF (RR = 1.06; 95% CI: 1.03-1.08) [39].…”
Section: Dose Of Alcoholmentioning
confidence: 59%
See 2 more Smart Citations
“…A relationship in the form of a "J" curve was found, as high alcohol consumption (>168 g/week) was significantly associated with an increased risk of AF, while moderate consumption (<168 g/week) was characterized by a protective effect [38]. However, the results of this meta-analysis were not confirmed in meta-analysis of 13 prospective studies, covering over 10 million subjects, conducted by Jiang et al [39]. This meta-analysis found that each increase in alcohol consumption by one drink/day is significantly associated with an increased risk of AF (RR = 1.06; 95% CI: 1.03-1.08) [39].…”
Section: Dose Of Alcoholmentioning
confidence: 59%
“…The most important results relating alcohol consumption and AF are summarized in Table 1 (Ref. [17,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]).…”
Section: Dose Of Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…LC_alcohol exhibited a positive association with AF. Alcohol consumption is a well-established co-risk factor for the development of AF [ 20 , 21 ]. Long-term alcohol intake induces progressive atrial structural remodeling [ 22 ], and acute alcohol consumption exerts direct cellular effects on atrial myocytes and influences autonomic nervous function, creating an electrophysiological environment conducive to AF initiation and maintenance [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation, the most common form of clinically relevant arrhythmia, increases the risk of serious health complications such as stroke, heart failure and overall mortality. In the context of alcohol, the scientific literature points to a variety of effects associated with different levels of consumption: from moderate to heavy [12][13][14][15][16].…”
Section: B) Alcoholmentioning
confidence: 99%